Risk analysis and management for projects. (Thomas Telford, 2002)
'Risk Analysis and Management for Projects' (RAMP) is a process that has been developed by a joint working party of the Institution of Civil Engineers and The Actuarial Profession for the purpose of evaluating and controlling risk in major projects. RAMP demonstrates how to identify, analyse and mitigate risks and how to place financial values on them.